2004
DOI: 10.1189/jlb.0703325
|View full text |Cite
|
Sign up to set email alerts
|

Mannose-binding lectin deficiency alters the development of fungal asthma: effects on airway response, inflammation, and cytokine profile

Abstract: Aspergillus fumigatus is a major fungal pathogen that may be fatal to immunocompromised individuals and causes airway hyperreactivity and remodeling in sensitized individuals. Herein, we examined the role of mannose-binding lectin (MBL), a complement-activating plasma protein, during pulmonary innate and allergic immune responses directed against A. fumigatus spores or conidia. Neither group of nonsensitized MBL-A-sufficient (MBL-A+/+) nor -deficient (MBL-A-/-) mice challenged with an intravenous or intratrach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
50
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(50 citation statements)
references
References 51 publications
0
50
0
Order By: Relevance
“…Increased MBL levels and activity in allergic patients attributed to the observed intronic polymorphism may contribute to increased complement activation via the lectin pathway, and hence to an increased severity of allergic markers such as an increase in blood eosinophil counts. Also, complement activation MBL may lead directly to the development of allergy by affecting the levels of proinflammatory cytokines [32]. A recent study on animal models of Afuinduced asthma by Hogaboam et al [32] showed that in Afusensitized murine MBL-A-deficient mice whole lung T helper cell type 2 cytokine levels were decreased significantly, and whole lung interferon-gamma levels were increased significantly when compared with normal mice, indicating that the murine MBL-A contributes to the development and maintenance of airway hyperresponsiveness.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increased MBL levels and activity in allergic patients attributed to the observed intronic polymorphism may contribute to increased complement activation via the lectin pathway, and hence to an increased severity of allergic markers such as an increase in blood eosinophil counts. Also, complement activation MBL may lead directly to the development of allergy by affecting the levels of proinflammatory cytokines [32]. A recent study on animal models of Afuinduced asthma by Hogaboam et al [32] showed that in Afusensitized murine MBL-A-deficient mice whole lung T helper cell type 2 cytokine levels were decreased significantly, and whole lung interferon-gamma levels were increased significantly when compared with normal mice, indicating that the murine MBL-A contributes to the development and maintenance of airway hyperresponsiveness.…”
Section: Discussionmentioning
confidence: 99%
“…Also, complement activation MBL may lead directly to the development of allergy by affecting the levels of proinflammatory cytokines [32]. A recent study on animal models of Afuinduced asthma by Hogaboam et al [32] showed that in Afusensitized murine MBL-A-deficient mice whole lung T helper cell type 2 cytokine levels were decreased significantly, and whole lung interferon-gamma levels were increased significantly when compared with normal mice, indicating that the murine MBL-A contributes to the development and maintenance of airway hyperresponsiveness. As well as the novel intronic SNP, the three exon 1 SNPs [G875A (B allele), G884A (C allele) and C868T (D allele)] at codons 54, 57 and 52, respectively, leading to low plasma MBL levels that have been reported in other populations including the Indian population, were also present in our study population [13,[33][34][35][36].…”
Section: Discussionmentioning
confidence: 99%
“…Although, MBL-A deficiency may cause complement-mediated changes in cellular activation status, we found no profound differences in splenic T cell cytokine responses to either parasites or OVA in the absence of MBL-A (although in some experiments we did observe increased IFN-␥ in MBL-A Ϫ/Ϫ mice). Previous work has shown that enhanced survival of MBL-A Ϫ/Ϫ mice in an acute septic peritonitis model correlated with decreased levels of both TNF-␣ and IL-6 in the blood and peritoneal cavity (18), while in contrast, MBL-A Ϫ/Ϫ mice had decreased Th2 responses and increased IFN-␥ during fungal-induced asthma (19). Human MBL suppresses the monocyte proinflammatory cytokines IL-1␣ and IL-1␤ and increases IL-10, IL-1R antagonist, MCP-1, and IL-6 following LPS stimulation in vitro (20).…”
Section: Discussionmentioning
confidence: 99%
“…Complement activation may be influenced by the antigenic structure of A. fumigatus strains, as clinical strains isolated from patients with invasive aspergillosis induced a stronger activation of the alternative pathway than did environmental strains (54). In the context of in vivo animal models, mannan-binding lectin is not necessary for antifungal defense in immunocompetent hosts, since mannan-binding lectin gene knockout mice are not susceptible to invasive aspergillosis (72). However, the administration of exogenous mannan-binding lectin to corticosteroid-treated mice with invasive aspergillosis resulted in improved survival and reduced lung fungal burden in infected mice.…”
Section: Soluble Receptorsmentioning
confidence: 99%